2003
DOI: 10.1046/j.1365-2265.2003.01740.x
|View full text |Cite
|
Sign up to set email alerts
|

GH‐secreting pituitary adenomas infrequently contain inactivating mutations of PRKAR1A and LOH of 17q23–24

Abstract: We reconfirm the important role of activating mutations of GNAS1 in GH-secreting adenomas, and conclude that PRKAR1A does not play a significant role in the tumourigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 30 publications
(47 reference statements)
2
28
0
1
Order By: Relevance
“…Subsequently, the same genetic defects have been detected in some sporadic endocrine tumors, such as adrenal and thyroid adenomas and carcinomas (16 -18). Conversely, a role of PKA R1A in the pathogenesis of pituitary tumors has been ruled out based on the absence of both gene mutations and loss of heterozygosity reported by previous studies and confirmed in the present series (15,19,20).…”
Section: Discussionsupporting
confidence: 58%
“…Subsequently, the same genetic defects have been detected in some sporadic endocrine tumors, such as adrenal and thyroid adenomas and carcinomas (16 -18). Conversely, a role of PKA R1A in the pathogenesis of pituitary tumors has been ruled out based on the absence of both gene mutations and loss of heterozygosity reported by previous studies and confirmed in the present series (15,19,20).…”
Section: Discussionsupporting
confidence: 58%
“…In studies reported in 1993, the incidence of gsp mutations in Japanese acromegalics was low as 9.3 and 4.4% (43,44); however, re-evaluation performed 10 years later by the same authors indicated that the corrected incidence was 53.1% (45).…”
Section: Gsp Mutations and Ck Staining Patternmentioning
confidence: 99%
“…A reduced expression and/or function of the protein kinase A (PKA) regulatory subunit type Ia (PRKAR1A) due to loss-of-function mutations, leading to an abnormal cAMP pathway activation, causes GH-secreting pituitary adenomas in Carney complex, an autosomal dominant familial syndrome (19,20). To date, mutations of PRKAR1A gene have been rarely found in sporadic pituitary tumors (21,22), although a reduced PRKAR1A expression resulting from increased proteasomal degradation has been described in sporadic GH-secreting tumors (10). Reduced cAMP degradation caused by mutations in PDE11A and PDE8B, coding for members of the phosphodiesterase (PDE) family, have been involved in adrenocortical hyperplasia, adenomas, and cancer as well as in testicular germ cell tumors (23,24).…”
mentioning
confidence: 99%